Financial Executive's Handbook - Vancil Richard F (Don Jones-Irwin, 1970)
List of Exhibits, The Financial Executive as a Member of the Top Management Team, The Financial Executive as the Administrator of a Major Corporate Function, Financial and Economic Analysis, Planning and Budgeting, Information Technology, Control and Measurement and Reporting and Evaluation of Operations, Asset Management and Control, Financial Structure, Financial Accounting Policies, External Relations, Index.